2018
DOI: 10.18584/iipj.2018.9.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Access to Skilled Jobs in the Canadian Forest Industry: The Role of Education

Abstract: In this article, the effect of education on the skill level of jobs held by Indigenous people working in the Canadian forest industry is examined. A skill index based on detailed occupation is used as the dependent variable in ordered logit models estimated using data from Statistics Canada’s 2011 National Household Survey (NHS). Results are obtained by gender. In the case of men, for Métis (a specific mixed European and Indigenous culture) and for First Nations living off reserve estimates of the effect of ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Mention was also made of the seasonal and precarious nature of many jobs in forestry and the impact on workers' ability to access the government EI program, a situation that can lead to stress and a disinterest in forestry jobs. This finding, much like Cahill's (2018), highlights the fact that recruiting this workforce requires more than the resources of organizations alone and must involve government authorities. However, policies could address this issue by working toward diversifying workers' sources of income or their versatility.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Mention was also made of the seasonal and precarious nature of many jobs in forestry and the impact on workers' ability to access the government EI program, a situation that can lead to stress and a disinterest in forestry jobs. This finding, much like Cahill's (2018), highlights the fact that recruiting this workforce requires more than the resources of organizations alone and must involve government authorities. However, policies could address this issue by working toward diversifying workers' sources of income or their versatility.…”
Section: Discussionmentioning
confidence: 78%
“…Also, social difficulties (violence, drug and alcohol abuse) caused by difficult living conditions can affect employability and limit or even prevent the integration of Indigenous people into the labour market (Reading and Wien, 2009). Considering that education level remains an important determinant of the quality of the job held and that holding a quality job strongly contributes to reducing socio-economic inequalities (Cahills, 2018), it is crucial that improving access to all levels of education for Indigenous people be at the core of concerns and human resources management policies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experts on the topic of Indigenous workforce development discuss many barriers that prevent Indigenous workers from entering or staying in the workforce or being included in the benefits of IBAs. These include barriers to formal education and lack of recognized job experience due to the historic segregation of the skilled trades (Cahill, 2018;Caron et al, 2019;Purdie et al, 2006), inaccessible application processes (Cahill, 2018;Sloan & Oliver, 2009), socio-economic disadvantages, physical distance from workplaces, commitment to traditional activities (Caron et al, 2019), and discrimination and racism in the workplace (Caron et al, 2019, Purdie et al, 2008. Others have also found that directly addressing these barriers to employment in resource extraction industries contributes to financial stability, helps develop skills, and potentially allows for participation in land management (Haley & Fisher, 2012;Loxton et al, 2012;Ritter, 2001).…”
Section: Government Brokered Cbasmentioning
confidence: 99%